DEVELOPMENT AND EVALUATION OF METFORMIN LIPOSOME FORMULATIONS - Kumar, Vijay; Joshi, Aparna; Kumar, KAPIL; Teotia, Deepak; Ikram; Khairya, Deepti (International Journal of Indigenous Herbs and Drugs, 2022)
This inquiry focuses on liposomes as its subject matter. Liposomes are an excellent means of increasing the period of time during which an impact is active from hours to months. In the current investigation, liposomal formulations of metformin hydrochloride were created and analysed by the researchers. Because its plasma half-life is much shorter than that of other drugs (t1/2 = 1.5 h), the patient has to take the drug more often in order to keep its concentration in steady state plasma. In this study, liposomal formulations of metformin were tested for drug entrapment, surface characterisation, in-vitro drug release investigations, release kinetics, and their underlying processes. Study concludes that the development of liposomal solutions of metformin hydrochloride was a fruitful endeavour.